Children's perception of other children with dental fluorosis - A cross-sectional study - Hanan Siddiq; Kalyana-Chakravarthy Pentapati; Shashidhar Acharya (Elsevier, 2020)
Background: Dental appearance may influence how others perceive individuals. This study would help to understand whether young people make judgments about other young people with dental fluorosis. Aim: We aimed to evaluate the perception of children aged 12-15 years about other children with visible dental fluorosis. Materials and methods: A self-administered social attribute questionnaire was used to capture dental appearance-related judgments of 455 children aged 12-15 years, from 6 schools. All the children were given either a set of full-face photographs of a boy and a girl, without dental fluorosis or digitally modified anterior teeth to show visible dental fluorosis. The Total Attribute Score (TAS) was measured by totaling the participant's ratings for each characteristic, ranging from 11 (most negative score) and 44 (most positive). Results: A total of 437 children participated, 53.8% (235) were males with a mean age of 13.99 ± 0.825. The mean TAS for photographs with fluorosis (25.9 ± 4.73) was significantly lower than without fluorosis (34.8 ± 4.83) (p < 0.001). Concerning gender, age, and SES, photos with fluorosis had significantly lower mean TAS than without fluorosis (p < 0.001, <0.001, <0.001 and < 0.001), respectively. Conclusion: Children in our study perceived that fluorosis could have a negative impact on their appearance.